2008
DOI: 10.1088/0957-4484/19/17/175604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of iodine molecular wires in channels of zeolite AEL single crystals

Abstract: Well-aligned iodine molecular wires were synthesized by means of loading iodine molecules in the elliptical nanometer-scale channels of AlPO(4)-11 (AEL) single crystals. Polarized Raman spectra reveal that the iodine molecular wires are oriented along the crystal channel direction by lining iodine molecules on the yz plane, where y and z represent the channel direction and the major-axial direction of the elliptical rings, respectively. Natural iodine wires are unstable, but they are very stable in the AEL cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 23 publications
5
27
0
Order By: Relevance
“…The iodine molecules are oriented along the major axis not the minor axis in AEL channels. This configuration is confirmed by molecular dynamics simulation as well as polarized Raman spectroscopy202128.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The iodine molecules are oriented along the major axis not the minor axis in AEL channels. This configuration is confirmed by molecular dynamics simulation as well as polarized Raman spectroscopy202128.…”
Section: Resultssupporting
confidence: 62%
“…We use aluminophosphate (AlPO 4 ) porous single crystals as the “molecular ruler”, which have been widely adopted as host template platforms since their ultra-small opening nano-channels are suitable to trap small guest molecules12131415161718192021. AlPO 4 single crystals are transparent from ultraviolet to near-infrared, which are appropriate for the optical investigation of the trapped guest molecules181920212223.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the frequency of an (I 2 ) n chain has been reported to show a significant upshift to 196 or 199 cm −1 when it is confined inside elliptic channels of silicaferrierite (0.42−0.54 nm, 10-member ring channels) 11 and AEL (0.44−0.67 nm). 12 It should be noted here that the elliptic channels can be taken as a 2D confinement environment compared with the size of iodine molecule, in which the rotation of I 2 can only occur along the long-axis of the elliptic cross section of the channel. Thus, the vibration of the iodine molecule is different from that in a round channel of AFI, due to different confinement effect.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous literatures reported that iodine species including chain‐like, lying, and standing iodine molecules are present in the elliptical nanochannels of AEL crystals at room temperature, and the corresponding wavenumber are located at 199 cm −1 , 207 cm −1 , and 214 cm −1 , respectively . Fig.…”
Section: Resultsmentioning
confidence: 77%